2023
DOI: 10.1002/jor.25549
|View full text |Cite
|
Sign up to set email alerts
|

Topical nonsteroidal anti‐inflammatory drugs for management of osteoarthritis pain: A consensus recommendation

Abstract: Osteoarthritis (OA) contributes to significant medical and socioeconomic burden in many populations. Its prevalence is expected to rise continuously owing to the combined effects of aging and increase in risk factors, including obesity, physical inactivity, and joint injuries. Pain is a hallmark presentation of OA. Topical nonsteroidal anti‐inflammatory drugs (NSAIDs) are recommended by many international guidelines as an early treatment option of the management of osteoarthritic pain. However, the use of topi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…As was outlined in the recent consensus article by Lee and colleagues in the Journal of Orthopaedic Research, topical nonsteroidal antiinflammatory drugs (NSAIDs) have become a first-line therapy for the treatment of pain associated with osteoarthritis (OA). 1 These recommendations for topical NSAIDs for OA are further supported by the formal clinical practice guidelines of the American Academy of Orthopedic Surgeons and the American College of Rheumatology. 2,3 As Lee et al point out, topical NSAIDs are indicated for reducing the pain and improving the function of OA because of ease of use, safety, and efficacy, thus, topical NSAIDs are recommended as firstline therapy for OA.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…As was outlined in the recent consensus article by Lee and colleagues in the Journal of Orthopaedic Research, topical nonsteroidal antiinflammatory drugs (NSAIDs) have become a first-line therapy for the treatment of pain associated with osteoarthritis (OA). 1 These recommendations for topical NSAIDs for OA are further supported by the formal clinical practice guidelines of the American Academy of Orthopedic Surgeons and the American College of Rheumatology. 2,3 As Lee et al point out, topical NSAIDs are indicated for reducing the pain and improving the function of OA because of ease of use, safety, and efficacy, thus, topical NSAIDs are recommended as firstline therapy for OA.…”
mentioning
confidence: 98%
“…2,3 As Lee et al point out, topical NSAIDs are indicated for reducing the pain and improving the function of OA because of ease of use, safety, and efficacy, thus, topical NSAIDs are recommended as firstline therapy for OA. [1][2][3] Diclofenac gel is the most commonly used topical NSAID worldwide, although multiple other NSAIDs have been used in many diverse vehicles including cream, foam, spray, ointments, plasters, and patches. [4][5][6][7][8] In clinical trials, NSAID patches with diclofenac, flubiprofen, loxoprofen, and other NSAIDs have been shown to be effective for OA pain although toxicity may be greater than strictly topical NSAID due to greater systemic absorption from the patch design.…”
mentioning
confidence: 99%
See 1 more Smart Citation